Marketing Problems Faced by Mulberry Growers:A Study in Erode District of Tamil Nadu - Selvaraj, A.; Vijaysanthi, K. R. (Indian Journal of Marketing, 2009)
More than 70% of the Indian population lives in the rural segment and depends on agriculture and its allied sectors for their livelihood-either directly or indirectly. The effect of green revolution in India has resulted in India becoming self-sufficient in food production. Present stress is to encourage the industry-mainly agro-based; which can fetch more and more foreign exchange to improve the balance of payment scenario of India. The change in the agricultural scene, viz., the scarcity of water and consequent difficult in cultivating water intensive crops like paddy and sugarcane, have led to marginalization of farm lands and subsequent decline in income from agricultural operation. Consequent to these changes, the social, economic and occupational scenes in the rural areas are changing from bad to worse. These circumstances become essential to explore viable alternatives for generating additional employment and supplementing the scanty income of the farm families. Sericulture is one among the several options that can be considered for rendering economic support to such facilities.